2017
DOI: 10.1002/fsn3.533
|View full text |Cite
|
Sign up to set email alerts
|

Toxicological parameters of albino rats fed with extruded snacks from Aerial yam (Dioscoria bulbifera) and African breadfruit seed (Treculia africana)

Abstract: In this study, safety of novel food from aerial yam and Treculia africana, underutilized food materials with high‐nutritive value and health benefits were investigated. Animal experiment involving the use of thirty (30) male albino rats was conducted for 28 days.Thereafter, rats in all groups were sacrificed and blood samples collected for biochemical analysis and hematological assay. Some vital organs were harvested and used for histological analysis. Biochemical and hematological parameters were not signific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 12 publications
2
3
0
Order By: Relevance
“…There were no significant pathological changes in liver and kidney of rats fed unfermented and fermented air potato. These results were in agreement with the report of Olatoye and Arueya (2018) who stated the hepatocytes in the liver showed no form of necrosis or lesions and any histopathological alterations and distortions. They appeared physically normal and healthy.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…There were no significant pathological changes in liver and kidney of rats fed unfermented and fermented air potato. These results were in agreement with the report of Olatoye and Arueya (2018) who stated the hepatocytes in the liver showed no form of necrosis or lesions and any histopathological alterations and distortions. They appeared physically normal and healthy.…”
Section: Discussionsupporting
confidence: 93%
“…The rats fed unfermented and fermented flours showed no sign of weakness or illness, the results of the hematological test showed that the unfermented and fermented flours have no significant effects on the packed cell volume, white blood cells, and hemoglobin. The blood cell parameters were very close to expected normal range reported by Olatoye and Arueya, (2018). There were no significant differences between differential count parameters of rats fed with experimental diet and those not fed with the diet.…”
Section: Discussionsupporting
confidence: 85%
“…The hematological status of the rats after 14 days of extract administration showed no significant differences ( p > .05) compared to that of control groups, except for anemia observed in infected and untreated female rats, possibly due to the effects of Salmonella infection. In another study carried out by Olatoye and Arueya ( 2018 ), whereby authors have evaluated the safety of aerial yam and Treculia Africana , Murine model involving 30 male albino rats was employed for time interval of 28 days. The blood samples of rats were then subjected to the hematological and biochemical assays followed by histological analysis.…”
Section: Resultsmentioning
confidence: 99%
“…Sanful and Engmann [7] qualified these tubers as raw materials used for the formulation of different food products. Olatoye and Arueya [8] reported that Dioscorea bulbifera has high agronomic yield, a condition that can boost the growth and socio-economic development of producers. According to Han et al [9], D. bulbifera flour has satisfactory organoleptic characteristics.…”
Section: Introductionmentioning
confidence: 99%